2014
DOI: 10.1038/srep03830
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's Jelly human Mesenchymal Stem Cell contact guidance by noisy nanotopographies

Abstract: The development of biomaterials ensuring proper cell adhesion, polarization, migration and differentiation represents a true enabler for successful tissue-engineering applications. Surface nanostructuring was suggested as a promising method for improving cell-substrate interaction. Here, we study Wharton's Jelly human Mesenchymal Stem Cells (WJ-hMSC) interacting with nanogratings (NGs) having a controlled amount of nanotopographical noise (nTN). Our data demonstrate that unperturbed NGs induce cell polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
(72 reference statements)
2
16
0
Order By: Relevance
“…All the COC surfaces were proven to be adhesive for MPCs without requiring any chemical functionalization but plasma activation. In this study and previously (Tonazzini et al, 2013; Jacchetti et al, 2014) we did not find any cytotoxicity originating by either the surface topographical modification or by the material itself. Finally, standard tissue culture Petri dishes were also used as control condition for the FLAT substrates in order to verify that the material itself did not cause the MPC-MSC transition.…”
Section: Resultssupporting
confidence: 75%
“…All the COC surfaces were proven to be adhesive for MPCs without requiring any chemical functionalization but plasma activation. In this study and previously (Tonazzini et al, 2013; Jacchetti et al, 2014) we did not find any cytotoxicity originating by either the surface topographical modification or by the material itself. Finally, standard tissue culture Petri dishes were also used as control condition for the FLAT substrates in order to verify that the material itself did not cause the MPC-MSC transition.…”
Section: Resultssupporting
confidence: 75%
“…Results from 2D cell cultures on planar substrates have previously led to values of 700 μm/day, while the use of micro-patterned grooves has promoted a velocity of up to 1000 μm/day and encouraged interest in using surface patterns to promote cell culture strategies [47]. Recent research has also demonstrated the beneficial use of anisotropic nanopatterns to drive stem cell migration and has shown cell velocity values of up to 960 μm/day along the direction parallel to the pattern and up to 600 μm/day along the direction perpendicular to the pattern [48]. The results are in accordance with the behavior of hMSCs.…”
mentioning
confidence: 99%
“…In the microsystem, hMSCs reach a velocity value of 6000 µm/day, helping to show the positive impact of incorporating design-defined fractal microtextures to promote cell motility and eventual tissue growth. Results from 2D cell cultures on planar substrates have previously led to values of 700 µm/day, while the use of micro-patterned grooves has promoted a velocity of up to Recent research has also demonstrated the beneficial use of anisotropic nanopatterns to drive stem cell migration and has shown cell velocity values of up to 960 µm/day along the direction parallel to the pattern and up to 600 µm/day along the direction perpendicular to the pattern [48].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,40 The degree to which cells engage in contact guidance is intimately related to the degree of collagen fiber alignment and consequently the noise in the contact guidance signal. 17,51 However, collagen fiber alignment dynamically changes over time due to both contractility and MMP activity of stromal cells in the tumor microenvironment. Cancer cells can also remodel collagen fibers during the process of migration.…”
Section: Discussionmentioning
confidence: 99%